Search-for-yield in Canadian fixed-income mutual funds and monetary policy - Sermin Gungor; Jesus Sierra (Bank of Canada, 2014)
This paper investigates the effects of monetary policy on the risk-taking behavior of fixed-income mutual funds in Canada. We consider different measures of the stance of monetary policy and investigate active variation in mutual funds' risk exposure in response to monetary policy. We find evidence in support of a systematic link between monetary conditions and intertemporal variation in the risk-taking behavior of mutual funds. Specifically, following an expansionary monetary shift, funds actively increase default-risk exposure (i.e., search-for-yield). This is particularly evident in the post-crisis period where interest rates were kept low for a prolonged period of time.
Keywords: G23; E52; 330; Financial institutions; Transmission of monetary policy